Effects of Smallholders’ on-Farm Water Application Methods on Tomato Yields in Baringo County, Kenya - Kosgei , David K. (African Journal of Education,Science and Technology (AJEST), 2018)
Baringo County experiences frequent rainfall failures, resulting in crop failures. This requires requisite on-farm water management. This study examined the effects of various water application methods on tomato, Solanum lycopersicum, yields of small-scale farmers in Baringo County. The study employed a descriptive survey design to collect data from target population of 672 households living within 10km of Marigat Town. Gross margins were highest in motor pump, followed by manual pump, gravity, and lastly, in rain fed; suggesting that all forms of irrigation were more profitable than rain fed agriculture in the farming of tomatoes. Semi log functions revealed that lift, gravity, seeds, DAP, CAN, and labour had a significant and positive effects (at p<.05) on tomato yields. The results suggested that the best on-farm water application regime was the lift system hence adoption of appropriate irrigation systems by farmers in areas with plentiful supply of water.